Designers' guide to Eurocode 1. EN 1991-1-1 and -1-3 to -1-7 - Gulvanessian, H. (Eurocode designers' guide series., 2009)
The design process of a bridge includes several steps. One of the major steps is the determination of actions & combinations of actions. These actions are imposed loads due to traffic climatic actions, actions due to water or soil subsidence construction loads & accidental actions.